Analysis of the individual travel insurance in the Czech Republic - Zdeněk Rybák (European Financial and Accounting Journal, 2018)
The main goal of this paper is to provide the description, current offer and factors behind the premia differences of the travel insurance products offered in the Czech Republic. It focuses on the premia pricing, risks covered, claim limits, product distribution and terms and conditions in comparison with the Central European region. Also, there are expressed findings, limitations and trends of this product. The paper first analyses the whole market of travel insurance. Next, it focuses on the travel insurance in general in order to provide the readers with some basic information. There is provided a description of the situation in the Czech Republic, such as the travel insurance with details on the risks covered, forms of the travel insurance, distribution channels, limits for the coverage, price factors (age, purpose of the trip, destination, length of the trip). The analysis is complemented by price analysis in order to provide the price factor overview to this product, with an expansion and comparison of prices within the Central European region. The final part of the paper discusses findings on the travel insurance and also provides current trends in the travel insurance industry of the Czech Republic.
Keywords: G20; G22; I13; 650; Czech Republic; Insurance; Risks; Travel insurance